Pelaksanaan Program Siaga Bencana Di Sekolah Menengah Pertama Pada Kawasan Rawan Bencana - F, Akhmad Ervin; Santoso, Apik Budi; Juhadi, Juhadi (Edu Geography, 2017)
The purpose of research to know the level of knowledge of school residents, school policy, planning school community preparedness, and mobilization of school resources in the implementation of standby school programs disaster. This research was conducted in SMP Negeri 2 Cangkringan Subdistrict Cangkringan Sleman. Data collection techniques used were tests, interviews, questionnaires, observations, and documentation. The analysis technique uses quantitative descriptive. The research results show the level of knowledge about disaster in the effort to face the eruption of Mount Merapi incident is very good, the school policy supporting disaster preparedness school programs including unfavorable sub-variables with 40% disruption, planning of school community preparedness in reducing and facing the risk of eruption of the mountain merapi including good with sub variable which fulfilled 88,89% and mobilization of school resources within disaster risk reduction efforts eruption of Mount Merapi including good with sub variable that fulfilled 85.71%. Tujuan penelitian untuk mengetahui tingkat pengetahuan warga sekolah, kebijakan sekolah, perencanaan kesiapsiagaan warga sekolah, dan mobilisasi sumberdaya sekolah dalam Pelaksanaan program sekolah siaga bencana. Penelitian ini dilakukan di SMP Negeri 2 Cangkringan Kecamatan Cangkringan Kabupaten Sleman. Teknik pengumpulan data yang digunakan adalah tes, wawancara, kuesioner, observasi, dan dokumentasi. Teknik analisis menggunakan deskriptif kuantitatif. Hasil Penelitian menunjukkan tingkat pengetahuan tentang bencana dalam upaya menghadapi bencana erupsi gunung merapi termasuk sangat baik, kebijakan sekolah yang mendukung program sekolah siaga bencana termasuk kurang baik dengan sub variabel yang terpenihi 40 %, perencanaan kesiapsiagaan warga sekolah dalam upaya pengurangan dan menghadapi risiko erupsi gunung merapi termasuk baik dengan sub variabel yang terpenuhi 88,89% dan mobilisasi sumberdaya sekolah dalam upaya pengurangan risiko bencana erupsi gunung merapi termasuk baik dengan sub variabel yang terpenuhi 85,71%.